Experience and attitudes towards e-learning among 1st year undergraduate students in health-related faculties during COVID 19 pandemic (Bangladesh Journal of Medical Education, 2024)
Objectives: The present study aimed to determine the experience and attitudes towards e-learning, contributory factors that influence the experience and attitudes towards e-learning among 1st year undergraduate students of Faculty of Dental Sciences (FDS), Faculty of Medicine (FOM), Faculty of Veterinary Medicine and Animal Sciences (FVMAS) and Faculty of Allied Health Sciences (FAHS) of University of Peradeniya, Sri Lanka during Covid 19 outburst.Methods: A Google form-based questionnaire was used, and 406 responses were received. The questionnaire had demographic data and socio-economic status of participants, accessibility to internet for online learning, perceived IT ability, English literacy, experience and attitudes of participants related to online learning. A point system was employed to give a score for the categorical data (IT literacy, English literacy, experiences, attitudes, and barriers). Data was analysed using SPSS Software (version 21).Results: This study revealed that students of FDS showed the highest average score for good experiences and attitudes towards e learning while FAHS displayed the lowest among health-related faculties. Furthermore, students of FDS experienced minimum level of barriers while those of FVMAS experienced many barriers during online learning. This study also showed that experiences, attitudes, and barriers towards online learning are highly variable and significantly different among the students of four health related faculties of University of Peradeniya.Conclusion: Students of all four health related faculties still prefer face- face learning over online learning due to several unpleasant experiences and attitudes and barriers that they have understood during online learning.BJME, Volume-15, Issue-02, July 2024: 3-26